2016
DOI: 10.1111/jop.12517
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chemically induced oral ulcer using adipose‐derived mesenchymal stem cell sheet

Abstract: Cell sheet technology using MSC can be an alternative treatment for oral ulcerations in that it can decrease healing time without invasive properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
1
24
1
Order By: Relevance
“…2A ), which was consistent with the clinical symptoms. CIM is another model applied for studying oral mucositis caused by cancer therapy 20 . Similarly, the expression levels of CXCL2 mRNA and protein were substantially increased in CIM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A ), which was consistent with the clinical symptoms. CIM is another model applied for studying oral mucositis caused by cancer therapy 20 . Similarly, the expression levels of CXCL2 mRNA and protein were substantially increased in CIM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, they have a good capability to differentiate toward both the adipogenic and the osteogenic lineage (Ardeshirylajimi et al, 2015; Ghaderi et al, 2018), providing a strong rationale for their use in maxillofacial surgery. Indeed, they have been adopted both for facilitating the healing of oral ulcers and for bone reconstruction procedures (Lee et al, 2017). Moreover, both harvesting and application of BFP into alveolar cavities or onto buccal soft tissues have proven to be safe and without any risk for the patient (Khojasteh & Sadeghi, 2016; Khojasteh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Within the last two decades, cell sheets of MSCs have been used in tissue engineering/tissue regeneration of several types of tissues and/or organs including (but are not limited to) the cornea [ 39 ], skin [ 40 , 41 ], cartilage [ 42 , 43 ], meniscus [ 44 ], bone [ 31 , 45 53 ], tendons [ 53 ], cardiac tissue [ 54 – 62 ], periodontal tissue [ 63 , 64 ], nasal epithelium [ 65 ], tooth [ 66 ], and blood vessel [ 67 ]. Cell sheets of MSCs have also been used in conditions such as wound healing [ 41 ], oral ulcers [ 68 ], digestive fistula [ 69 ], and spinal cord defects [ 70 , 71 ]. It has also been demonstrated that MSC sheets can induce angiogenesis in ischemic and/or wound tissues [ 41 , 72 ].…”
Section: Mesenchymal Stem Cells and Their Use In Cell Sheet-based mentioning
confidence: 99%